Interactive Patient-specific Vascular Modeling with Sweep Surfaces - Kretschmer, Jan; Godenschwager, Christian; Preim, Bernhard; Stamminger, Marc (IEEE Transactions on Visualization and Computer Graphics, 2013)
The precise modeling of vascular structures plays a key role in medical imaging applications, such as diagnosis, therapy planning and blood flow simulations. For the simulation of blood flow in particular, high-precision models are required to produce accurate results. It is thus common practice to perform extensive manual data polishing on vascular segmentations prior to simulation. This usually involves a complex tool chain which is highly impractical for clinical on-site application. To close this gap in current blood flow simulation pipelines, we present a novel technique for interactive vascular modeling which is based on implicit sweep surfaces. Our method is able to generate and correct smooth high-quality models based on geometric centerline descriptions on the fly. It supports complex vascular free-form contours and consequently allows for an accurate and fast modeling of pathological structures such as aneurysms or stenoses. We extend the concept of implicit sweep surfaces to achieve increased robustness and applicability as required in the medical field. We finally compare our method to existing techniques and provide case studies that confirm its contribution to current simulation pipelines. © 2013 IEEE.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD9.intera_8
Keywords: centerline-based modeling; Surface modeling; vascular visualization